Advances in Human Factors and Systems Interaction Proceedings of the AHFE 2018 International Conference on Human Factors and Systems Interaction, July 21-25, 2018, Loews Sapphire Falls Resort at Universal Studios, Orlando, Florida, USA - Nunes, Isabel L.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2019)
This book reports on cutting-edge research into innovative system interfaces, highlighting both lifecycle development and human-technology interaction, especially in virtual, augmented and mixed-reality systems. It describes advanced methodologies and tools for evaluating and improving interface usability and discusses new models, as well as case studies and good practices. The book addresses the human, hardware, and software factors in the process of developing interfaces for optimizing total system performance, particularly innovative computing technologies for teams dealing with dynamic environments, while minimizing total ownership costs. It also highlights the forces currently shaping the nature of computing and systems, including the need for decreasing hardware costs; the importance of portability, which translates to the modern tendency toward hardware miniaturization and technologies for reducing power requirements; the necessity of a better assimilation of computation in the environment; and social concerns regarding access to computers and systems for people with special needs. The book, which is based on the AHFE 2018 International Conference on Human Factors and Systems Interaction, held on July 21-25, 2018, in Orlando, Florida, USA, offers a timely survey and practice-oriented guide for systems interface users and developers alike.
Part I: Applications of Human Factors and System Interactions -- Relationships between cognitive workload and physiological response under reliable and unreliable automation -- Analysis of trust in automation survey instruments using semantic network analysis -- The antecedents of intelligent personal assistants adoption -- Research on comparison experiment of humanized interface design of smart TV based on user experience -- Part II: Human Factors and System Interactions in Complex Systems -- Moving forward with autonomous systems: Ethical dilemmas.
Keywords: Computational intelligence; User interfaces (Computer systems).; Human-computer interaction; Electronics; Computational Intelligence; User Interfaces and Human Computer Interaction; Electronics and Microelectronics, Instrumentation